Pemanfaatan Instagram Sebagai Media Promosi Jasa Tata Rias Pada Risa Vonda Make Up & Henna di Bukittinggi - Rahma Dini; Tomi Hendra (Lembaga Pengembangan Kinerja Dosen, 2024)
This research uses qualitative descriptive research. The data collection method was carried out using interviews and observation. Based on the results of research conducted regarding